Ensino de solos e educação ambiental: análise do uso das práticas ambientais no ensino fundamental (anos finais) - Suptitz, Marina Pereira da Silva (2021)
The teaching of Geography, until it became a curricular subject, it bad undergone thought several transformations in recent decades. Its contents have been changing its identity over the years. Several were the contents that stood out in this process, however there is a lack of interest in the Soil content, a fact that can be understood by the absence of the theme integrated into Basic Education and its theoretical knowledge does not complement Environmental Educational Practices developed in the school context. It should be noted here that in the process of teaching and learning Geography, this content is usually worked in a compartmentalized way, aimed at the agricultural economy. But, it is reinforced in this paper that there is a need to work it in one an integrated and interconnected way. In this context, a proposal of this research was to investigate if the Environmental Educational Practices, contemplated in the PPP (Political Pedagogical Project) and developed in the school context, are satisfactory to fundamentalize the importance of using the Soil content in Elementary School (Final Years). For its development, it was used the qualitative research methodology, seeking to identify and analyze the environmental educational practices carried out in the Geography discipline in Elementary School - Final Years, at Colégio Estadual Marechal Gaspar Dutra, municipality of Nova Santa Rosa-PR. The aim was to verify the relationship between Soil content and Formal Environmental Education. Likewise, it was intended highlight the characteristics and importance of teaching Soil in the Brazilian school context, identify and analyze the environmental educational practices developed in the Final Years of Elementary School, in order to assess its applicability trie to the presented teaching in the Geography and indicate the soil contents to environmental educational practices in addressing the Environment theme, seeking to analyze their importance and their creation in the student's social and economic context. With an exploratory nature, the following techniques were chosen for data collection: bibliographic survey and documentary/photographic analysis. For an analysis of the information, the Content Analysis technique was used, discussing what is proposed and what is actually done in the daily school life, in relation to Environmental Educational Practices on Soil. Therefore, it is expected to verify which Environmental Educational Practices make use of the Soil content as an understanding of the Environment.